Public and private media coverage of the military coup in Zimbabwe - Pedzisai Ruhanya; Trust Matsilele (World of Media, 2022)
This qualitative study examines coverage by Zimbabwe’s media of the events surrounding the military coup of November 2017. The study investigates 38 selected stories; 16 from the state controlled The Herald and 22 from the private owned Newsday newspapers. The sampled articles were considered relevant to the ‘military assisted political transition’ that took place in the period under study. Critically, the study is aimed to understand how events that transpired during the transitional period leading to President Robert Mugabe ouster, after three decades in power, have shaped journalism practice in Zimbabwe. Considering that the transitional period marked a major turning point in Zimbabwe’s political life, this study seeks to understand the role played by the country’s private and public media. In this paper, the authors try to find out who the two newspapers wrote about during the coup period, why the two normally opposite newspapers converged against Mugabe and how they framed his demise. Framing theory is used as an analytic lens of the study. The theory analyses meanings of statements, language and words used by the two newspapers. The study found out that, in an unusual situation, the newspapers reported a similar language and tone, demonstrating media convergence between a state-controlled newspaper and a private and oppositional publication that never existed since the country had gained independence in 1980. The study also observed that these media outlets violated journalistic ethics of fairness and right to reply as they saw the toppling of President Mugabe as crucial to the progress of the country.